Lifelong Learning in Tourism and Hospitality: Breakthrough European and Asian Experience - Rodionova E. V. Elena Viktorovna; Agranovich V. B. Viktoriya Borisovna; Konyukhova T. V. Tatiana Vasilievna; Biryukov D. K. Dmitry Konstantinovich; Melnikova V. G. Valentina Grigorjevna (2016, 2016)
Title screen